2011
DOI: 10.5902/198050984520
|View full text |Cite
|
Sign up to set email alerts
|

Sistemas de manejo em plantios florestais de eucalipto e perdas de solo e água na região do Vale do Rio Doce, MG

Abstract: RESUMOA erosão hídrica é a principal responsável pela perda da capacidade produtiva dos solos sob florestas plantadas e alteração da quantidade e qualidade da água em sub-bacias. Assim, este trabalho objetivou avaliar a influência dos sistemas de manejo adotados nos plantios florestais com eucalipto (eucalipto em nível -EN, eucalipto em desnível -ED e eucalipto em desnível com queima -EDQ) sobre as perdas de solo e água por erosão hídrica em relação às perdas em floresta nativa (FN), pastagem (PP) e solo desco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0
22

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 6 publications
2
14
0
22
Order By: Relevance
“…In eucalyptus plantations implanted with conservation practices, soil losses are much lower than those implanted with non-conservationist systems, as reported by Silva et al (2011). The authors observed 80% reduction in soil losses in a Red-Yellow Latosol due to the crop residues in the area, and 88% reduction in soil losses in a system where eucalyptus plantation was contour-planted.…”
Section: Introductionsupporting
confidence: 57%
“…In eucalyptus plantations implanted with conservation practices, soil losses are much lower than those implanted with non-conservationist systems, as reported by Silva et al (2011). The authors observed 80% reduction in soil losses in a Red-Yellow Latosol due to the crop residues in the area, and 88% reduction in soil losses in a system where eucalyptus plantation was contour-planted.…”
Section: Introductionsupporting
confidence: 57%
“…Namely: Cardoso et al (2004) and Martins et al (2010) in the state of Espirito Santo, Brito et al (2005), Pires et al (2006), Silva et al (2011) and Silva et al (2014) in the state of Minas Gerais, Cândido et al (2014), in Mato Grosso do Sul, and Oliveira et al (2013) in Rio Grande do Sul.…”
Section: Introductionmentioning
confidence: 99%
“…De acordo com Silva et al (2011), preparos conservacionistas e sistemas de manejo relacionados aos diferentes tipos de cobertura e preparos do solo, proporcionam uma maior eficiência no controle da erosão hídrica. A cobertura do solo é uma prática recomendada para as regiões semiáridas, uma vez que contribui para o desenvolvimento das culturas, reduz a perda de água e diminui a erosão superficial (Souza et al, 2008).…”
Section: Introductionunclassified